ANDIE'S AMBITION TO BE A BREAK DANCER REFLECTED IN STEP UP 2 THE STREET MOVIE (2008) DIRECTED BY JON M. CHU: A PSYCHOANALYTIC APPROACH - Rosyid, M. Nur (2011)
The movie is set in Baltimore, Maryland. It follows Andie West (Briana Evigan) as she pursues her big dream of becoming a street dancer. Her mother died of cancer when Andie was 16; she now lives with her mother's best friend, Sarah (her guardian), but in reality, Andie feels like she does not belong anywhere. Although she is doing badly at school, it is her dream for dancing that brings something special into her life. She trains with her dance crew, the "410" (pronounced four-one-oh, as in the area code for Baltimore), to keep the title of the illegal competition, 'The Streets.' Sarah is aware of the crime and harassment by the 410 and threatens to send Andie to live with her aunt in Texas if she doesn't change. Tyler (Channing Tatum) meets her at the dance club, The Dragon. Tyler tries to persuade her to audition for the Maryland School of the Arts (MSA), where Andie has to compete for a place, thinking it will help her life as it did his. Tyler decides to battle her for it. Tyler wins the battle and the two head back to Andie's house where Tyler asks Sarah to let her join MSA. Sarah eventually agrees, and Tyler leaves Andie to audition at MSA while he goes on tour with Nora. Chase Collins (Robert Hoffman) persuades the school director (his brother) Blake (Will Kemp) to recruit Andie after seeing her audition. When Andie's studies come before the crew, the members are angry and decide to kick her out. Andie and Chase form a new crew with help from many people Chase knows at the school, all of not accepted as who they are, including Andie's new friend Moose (Adam G. Sevani). Chase has a copied key to the studio and the crew secretly practices their routine late at night when the school is empty. They perform at the local dance club, but are rejected and kicked out. Andie's friend Missy Serrano (Danielle Polanco) joins the crew after going out of the 410 following the event, as she is disgusted by the crowd's reaction. Missy tells the crew that the only way to enter The Streets is to first pull a prank and post it on the Internet to show that the crew is entering the competition. Wanting revenge for being humiliated before, Chase decides that their prank will be to make a fool out of Tuck, the leader of the 410. The crew goes to a family barbecue at Missy's house, Sophie (MSA student who happens to have a crush on Chase) (Cassie Ventura), tags along. She begins to develop a crush on Moose after salsa dancing with him. The 410 doesn't like the fact that they have a new crew to compete with so they warn Andie's group to stay out of The Streets or there will be consequences. When Tuck finds Chase, he assaults him for his prank and warns him to stay away from The Streets and Andie. Chase comes into school the next day badly bruised and hurt. On top of that, the dance studio has been trashed by the 410 the previous night. Director Collins decides that he will not allow anyone from the school to be involved in illegal competitions. He then decides to expel Andie from MSA because of her involvement with the Streets competition after a tip-off from Sophie. When asked if there were any other students involved, Andie does not tell him about her crew. When Sarah hears the news of Andie's expulsion, Andie tries to explain, but Sarah refuses to listen, telling her that she has had enough of her behavior and that Andie now must go to live with her aunt in Texas. Just when Andie is packing her bags to leave, she receives a text message from Missy that The Streets is on that night - the same night as the MSA fundraiser. Along with Andie, her whole crew gets the text message. They decide to ditch the MSA fundraiser (except for Moose) and instead compete in The Streets. Sarah hears about what Andie did to protect her crew and is proud of her. She allows Andie to compete at The Streets with her crew. Chase also leaves the fundraiser hoping to win back Andie. When Collins notices that his students are gone, he questions Sophie. Moose tells him that he is in the crew and where they are which Moose took both Collins and Sophie to the place, they are timely for the crew's performance. The director, Blake, sees them and realizes that The Streets he was hearing and thinking about, is in fact a legitimate form of artistic expression. He accepts Andie into MSA again and tells Moose that he might be in the wrong department, suggesting that he wants Moose to come to MSA when he is able to. To Moose's surprise, he gets kissed by Sophie. With Andie's crew being supportive friends and her education now secured, the film finds its optimistic ending - a passionate kiss between Andie and Chase.